Jordanian women's (studying or working in medical fields) awareness in terms of the use of dental imaging during pregnancy - Ammar A. Oglat; Hanan Hasan (BMC, 2022)
Abstract Background The anxiety among pregnant women about the imaging of teeth during pregnancy may have an adverse effect on the oral health of both the mother and the fetus too. This research study was conducted to evaluate women's knowledge of the utilization of dental imaging during pregnancy. Methods In this research, structured questionnaires were distributed electronically through social media. The questionnaires contained questions focused on the women's (studying or working in medical fields) awareness regarding the ionizing radiation protection that takes place during dental imaging, the safest period for dental imaging, the sort of radiographs that can be required, and the chance of radiation-induced malignant tumor and malformation of the fetal as a result of dental imaging. Results Overall, 984 participants completed questionnaires that were analyzed after being received. Most of the participants (n = 637; 64.7%) were < 30 years of age. The greater number of the participants (66.8%) had fair knowledge of dental imaging. 25.4% mentioned that pregnant women are able to do dental imaging during the first trimester. And approximately half of the participants thought that cone-beam computed tomography and panoramic images must not be carried out during pregnancy. Moreover, nearly the same percentage of them also believed that the risk of inborn malformation is high due to dental imaging. Conclusions The results refer to a low awareness among people who have medical knowledge regarding dental radiograph protection during pregnancy. This needs to be paid attention to among students, graduates, and workers in medical fields by focusing on the courses and lectures related to dental imaging protection during pregnancy.